The Impact of Supply Chain Management as Mediator between Strategic Orientations and Supply Chain Performance - Yuhainis Mohd Yusoff; Hasbullah Ashari; Mohamed Najib Salleh (International Journal of Supply Chain Management, 2016)
Studies in supply chain have stated that strategic orientation can be employed to enhance supply chain performance (SCP). However, in the effort of enhancing SCP, there are still on-going issues such as, supply chain coordination, bullwhipped effect, information sharing and collaborative behaviours that need to be managed well. Therefore, in order to manage the issues, several authors have recommended supply chain management (SCM) to mediate the relationship between strategic orientation and SCP. SCM offers the opportunity to capture the synergy of intra and intercompany integration. The importance of SCM as a mediator can be considered as an important element to increase performance. Therefore, this conceptual paper proposes to study the importance of SCM as a mediator to SCP. It further explores the relationship of strategic alignment between two strategic orientations: market orientation (MO) and supply chain orientation (SCO). To investigate the strategic alignment relationship, this study proposes the complementary approach. The relationship and the complementary approach can be empirically tested for future research.